Favorite fairy tales told in Spain - Haviland, Virginia, 1911- (New York : Beech Tree Books, 1995)
A collection of tales from Spain
The Flea -- Four Brothers Who Were Both Wise and Foolish -- The Half-Chick -- The Carlanco -- Juan Cigarron -- The Enchanted Mule
Keywords: Fairy tales -- Spain; Folklore -- Spain